(untitled) (LEARNing Landscapes, 2014)
Addressing Hannah Arendt’s call to prepare the next generation to "renew our common world," this essay questions how we can simultaneously share our world with students and encourage them to question it. Because teacher education is suffocating in the stipulations of "best practices" that blanket the ambiguity that makes it interesting, this essay explores the questions that make this work compelling. It considers the inhibitions that constrain agency and imagination in teaching, the narratives that collapse experience into predictable accounts delivered to satisfy rubrics and protocols, and turns to the work of poet and classicist, Anne Carson, for a sense of story that opens up experience instead of closing it down.